Assessment of factors affecting social media use for HIV and AIDS communication among undergraduate students in South-Western Nigeria (2017)
The study evaluated factors that affect use of social media for HIV and AIDS communication among federal university undergraduates in south western Nigeria. The cross-sectional research method was employed. Structured questionnaire copies were administered to 355 undergraduate students. Quantitative data gathered from the administered questionnaire were analyzed using descriptive and inferential statistics. Result showed that blogs (41.1%), twitter (25.4%) and WhatsApp (17.7%) were the social media sites preferred by male and female respondents for sharing and accessing HIV and AIDS information. The use of these social media sites for HIV and AIDS information communication was influenced by privacy and neutrality. It also showed that majority of the undergraduates affirmed that HIV and AIDS information on social media platforms was very useful because it facilitated access to quality tips on HIV. A significant percentage of the respondents also affirmed that the use of social media was hugely affected by epileptic nature of power supply, poor network connectivity, ICT skills and cost of subscription. Stepwise multiple regression analysis identified ICT skill as the only environmental factor that had significant influence on social media use (F= 4.234, p<0.05) and was responsible for 33.9% of the variation in social media use for HIV information communication. The study suggested the campaign on prominent HIV/AIDS discussion sites and ICT skill acquisition to enable youth connect and effectively make use of social media for HIV information communication.